Deteksi Perubahan Tutupan Lahan menggunakan Citra Planetscope di Desa Pandiri Kecamatan Lage Kabupaten Poso - Laia, Berkat; Muis, Hasriani; Misrah, Misrah; Hulu, Amati Eltriman (Universitas Pattimura, 2025)
Land cover change reflects the dynamics of spatial use and the environmental condition of a region. This study aims to detect land cover changes in Pandiri Village, Lage District, Poso Regency, using PlanetScope satellite imagery acquired in 2019 and 2024. Land cover classification was performed using the Maximum Likelihood Classification (MLC) method, while change detection was conducted through a post-classification comparison of the resulting classified maps. The results identified six primary land cover classes: forest, dryland agriculture, open land, settlement, paddy fields, and water bodies. Over the 2019–2024 period, forest area decreased by 88.46 hectares, and dryland agriculture declined by 31.35 hectares. Conversely, increases occurred in open land (44.21 ha), settlement (24.23 ha), paddy fields (25.99 ha), and water bodies (25.38 ha). Accuracy assessment yielded an overall accuracy of 96.67% with a Kappa coefficient of 0.95, indicating a highly reliable classification. These findings confirm the capability of PlanetScope imagery in detecting village-scale land cover changes. The outcomes of this study are essential for supporting the evaluation of spatial planning policies and controlling land conversion to achieve sustainable natural resource management.